DIRECT DETECTION OF TRITERPENOID SAPONINS IN MEDICINAL PLANTS - Kareru, P. G.; Keriko, J. M.; Gachanja, A. N.; Keni, G. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Direct detection of saponins in medicinal plants using Fourier Transform Infrared (FTIR) spectroscopy is reported in this paper. Crude dry plant powders were mixed with potassium bromide (KBr) powder and compressed to a thin pellet for infrared examination. FTIR spectra of the test samples showed –OH, -C=O, C-H, and C=C absorptions characteristic of oleanane triterpenoid saponins. The C-O-C absorptions indicated glycoside linkages to the sapogenins. Phytochemical analysis confirmed the presence of saponins in the tested specimens. Entada leptostachya was used as a reference sample. Dry plant powder was extracted sequentially with hexane, dichloromethane, ethyl acetate and methanol. FTIR spectra of the reference sample powder and its organic solvent extracts showed characteristic saponin absorption peaks. These results indicated that direct detection of saponins in medicinal plants was possible by infrared analysis. Lengthy exhaustive chemical analyses necessary for detection of saponins could be avoided.